Reciprocal effects in true potato seed breeding in short-day length environments - Golmirzaie, A.; Ortíz, R. (Wiley, 2003)
Reciprocal crosses may have significantly distinct performances regarding tuber characteristics in potato, suggesting the importance of cytoplasmic effects in this crop. The selection of parents for true potato seed breeding therefore needs to consider this potential effect when determining the direction of a cross. The aim of this research was to determine whether a broad-based true potato seed breeding population, developed at the Centro Internacional de la Papa, could be affected by cytoplasmic effects in the short-day length environments of the tropics. Two random sets of reciprocal biparental crosses were included in the first set of experiments, which were grown in two contrasting Peruvian locations. Only one out of 14 reciprocal crosses showed significantly distinct performance for tuber yield and tuber set. In the second set, only one of each of the 12 reciprocal crosses had distinct performance for vine earliness, days to flowering and flowering intensity, but four of the reciprocal crosses in the second set showed distinct pollen production. The results suggest that cytoplasmic effects in this breeding population are more important for reproductive characteristics such as pollen production than for tuber yield. This finding is not surprising because male sterility in potato results from the interaction between sensitive cytoplasm and dominant nuclear genes